Global trends in antimicrobial resistance of Enterococcus faecium: a systematic review and meta-analysis of clinical isolates - Huang, Chen; Moradi, Samaneh; Sholeh, Mohammad; Tabaei, Faezeh Motallebi; Lai, Tingting; Tan, Bo; Meng, Jingjing; Azizian, Khalil (Frontiers in Pharmacology, 2025)
BackgroundMultidrug-resistant bacteria are associated with a high number of deaths and pose a significant global concern. In recent decades, among these resistant bacteria, Enterococcus faecium, a hospital-acquired pathogen, has attracted more attention.ObjectiveThe present study aims to document the current state of resistance in E. faecium globally by considering several variables, including geographical locations, temporal trends, and sources of infection.MethodsWe searched studies in PubMed, Scopus, and Web of Science (30 November 2022). All statistical analyses were carried out using the statistical package R.ResultsOur meta-analysis of antibiotic resistance across various clinical isolates revealed substantial heterogeneity and variability. The average resistance proportions ranged from 2% for linezolid to 62.8% for erythromycin, with significant differences observed across different time periods, countries, and World Health Organization regional offices.ConclusionOur findings confirm the high antibacterial activity of linezolid against E. faecium isolates. Additionally, our investigation reveals a gradual increase and a concerning upward trend in resistance rates for nearly all agents in recent years. However, the significant reduction in resistance rates for certain antibiotics suggests that these drugs could potentially regain their effectiveness in the future.